Land Use Planning in Metro Manila and the Urban Fringe: Implications on the Land and Real Estate Market - Marife M. Ballesteros (Philippine Institute for Development Studies (PIDS), 2000)
This paper examines land use planning in Metro Manila and the urban fringe and analyzes its effect on transactions in the urban land and real estate market. The analysis begins with a historical review of land use planning strategies in the metropolitan area and the attendant bureaucratic changes that occurred. The effects of these planning strategies on the urban land and real estate market are then analyzed using the transaction cost framework of the new institutional economics (NIE). It is argued that transaction costs in the land and real estate market in the Philippines has been significant due to the confusion brought about by unclear land use policies of the government. These costs have been noted to increase as government shifted from an interventionist and centralized system to a liberal and decentralized system of land use planning. The system of permits and licensing has become more complicated and inefficient overtime. To economize on transaction costs, real estate development companies engage in a lot of contracting and sub-contracting in the market. Relational contracting in the forms of "grease money and procedural short-cuts has been common to obtain development approvals. The high transaction costs are reflected in the prices of urban real estate. While Metro Manila has the lowest per unit costs of construction among neighboring cities in Asia, the high transaction costs make housing more expensive in the country than elsewhere in Asia. Contradicting policies on Philippine land use have to be corrected. Moreover, stronger and more direct government presence in the land and real estate market through land use planning and urban management seems necessary.
Keywords: 330; land use planning; urban management; real estate; Landnutzung; Suburbanisierung; Immobilienmarkt; Manila